Bile Duct Reconstruction: Results of Various Techniques - Siddique Ahmad, Muhammad Alam, Ali Gohar Khan, Rizmi Tahir, Sheema Amin, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Due to the complex nature and diversity of bile duct injury (BDI) controversy exists regarding the best management plan of BDIs and sometimes this problem may be difficult to be managed even in the hands of an experience surgeon. Aim: To evaluate different procedures used in the management of bile duct injuries Study Design: Prospective cohort study Place and Duration of Study: General Surgical Department, Hayatabad Medical Complex KPK, Pakistan from 1st January 2016 to 31st December 2020. Methodology: Twenty five patients were enrolled for appropriate management of bile duct injuries. The age range was 15-70 years. Results: Seven (28%) were males and 18 (72%) were females with mean age was 42 year. CBD injury occurred in 17 (68%) patients after open and 8 (32%) after laparoscopic cholecystectomy. Majority of the patients presented with obstructive jaundice 76% and bile leak 16%. Other presentation include biliary peritonitis, biloma, cholangitis etc were 8%. Fourteen (56%) patients had type E injuries and underwent Roux-en-y hepatico-jejunostomy. No patient presented with major bile leak or disruption of anastomosis. Minor leak occurred in 4 (16%), wound infection in 6 (24%), bleeding in 1 (4%), pulmonary embolism in 1 (4%). Conclusion: Simple bile duct injuries can be treated with lateral repairs however for more major injuries Roux-en-y hepatico-jejunostomy can produce satisfactory results depending on Strasberg-classification and bile duct status. Keywords: Reconstruction, Roux-En-Y hepaticojejunostomy, Bile duct injuries, Biliary stricture